The Perinatal and Maternal Outcomes of Instrumental Vaginal Delivery: Perinatal & Maternal Outcomes of Instrumental Vaginal Delivery - Alwazzan, Ahmed (Pakistan Journal of Health Sciences, 2023)
Instrumental vaginal delivery is necessary under special circumstances to facilitate a safer delivery process. Objective: To assess the perinatal and maternal outcomes of instrumental vaginal delivery. Methods: This retrospective study was conducted at King Abdul-Aziz University Hospital, Jeddah, Saudi Arabia and included patients from July 2018-June 2021. All females with singleton pregnancy who underwent instrumental delivery using vacuum or forceps were included. Data were analyzed using SPSS 19. Results: There was a total of 346 instrumental delivery cases during these three years, out of which 337 (97.4%) were vacuum and 9 (2.6%) were forceps. A significant difference was observed between both groups regarding 3rd & 4th-degree tears and hospital stay, where the mean hospitalization and the rate of 3rd & 4th-degree tears were higher among forceps groups than the vacuum group (4.1±2.8 forceps vs 2.1±1.0vacuum, p value<0.0001) and (44.4% forceps vs 9.5% vacuum, p value=0.009) respectively. There was a significant difference between the two groups regarding Apgar score at 1 m and Apgar score at 5 m, where the means of both Apgar scores were higher among the vacuum group than the forceps group (8.1±1.6 vacuum vs 6.4±3.2 forceps, p value=0.002) and (9.5±1.3 vacuum vs 8.3±3.2 forceps, p value=0.006) respectively. Conclusions: It is critical to renovate the training and use of operative vaginal delivery to improve these skills which is underutilized today. When it is performed by a skilled provider it is a perfect alternative to Caesarean delivery in the chosen patients.